DISCUSSÃO CURRICULAR A PARTIR DO TEMA ENERGIA NUMA PERSPECTIVA DE INTERVENÇÃO NA FORMAÇÃO CONTINUADA DE PROFESSORES - BENITE, Claudio Roberto Machado (2009)
The main purpose of this work was the investigation of public high school s teachers participation in various disciplines, in meetings to discuss curriculum, based on the theme energy, located in the city of Goiânia. This is a project included in a partnership university / school, in the perspective of new ways of intervention in their own practice. Starting from these assumptions is essential to highlight the role of nuclear research as the Center for Research in Science Teaching - NUPEC of IQ / UFG in environments such as school aggregate; therefore, the asymmetric relationship between the components allows both the collective and the individual growth. Whereas the theoretical and practical knowledge build the professional knowledge, this research is configured as an innovative alternative in the Teaching of Science during the execution of the project entitled "Construction of a solar collector with alternative materials: an experience in clean energy at the high school , aiming the increase of students' interest in natural and the engineering sciences, and the intention to motivate of school s teachers to adopt more stimulating science education practices. The data from this study, which has elements of a participatory research, are collected from the analysis of transcripts of six planning meetings recorded on VHS. The conclusion extracted from data analysis was that teachers find difficulties in getting engaged in activities other than those which constitute the everyday school life. At the same time we can see the potentiality that this type of approach - University / School - has in the perspective of developing new proposals of education and conclude that when supported by more experienced partners and backed up by school administration, teachers propose, discuss develop and carry out new pedagogical practices.